2015
DOI: 10.1128/aac.04494-14
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Monoclonal Antibodies Specific to the Lipopolysaccharide O Antigen from Multidrug-Resistant Escherichia coli Clone ST131-O25b:H4 Elicit Protection in Mice

Abstract: The Escherichia coli sequence type 131 (ST131)-O25b:H4 clone has spread worldwide and become responsible for a significant proportion of multidrug-resistant extraintestinal infections. We generated humanized monoclonal antibodies (MAbs) that target the lipopolysaccharide O25b antigen conserved within this lineage. These MAbs bound to the surface of live bacterial cells irrespective of the capsular type expressed. In a serum bactericidal assay in vitro, MAbs induced >95% bacterial killing in the presence of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…The MAC has an essential role in human immune protection against Gram‐negative bacteria; this is evident from recurrent infections in patients lacking MAC activity due to genetic deficiencies (Ram et al , ; Turley et al , ) or due to treatment with complement‐inhibitory drugs (Konar & Granoff, ; McNamara et al , ; Ricklin et al , ). Since MAC‐dependent cell lysis can be specifically triggered via antibodies, this killing mechanism is also exploited for therapeutic development of antibodies that target cancer cells or drug‐resistant bacterial infections (Szijártó et al , ; de Jong et al , ). Despite its crucial role in immunity, it is currently not understood how the MAC kills bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The MAC has an essential role in human immune protection against Gram‐negative bacteria; this is evident from recurrent infections in patients lacking MAC activity due to genetic deficiencies (Ram et al , ; Turley et al , ) or due to treatment with complement‐inhibitory drugs (Konar & Granoff, ; McNamara et al , ; Ricklin et al , ). Since MAC‐dependent cell lysis can be specifically triggered via antibodies, this killing mechanism is also exploited for therapeutic development of antibodies that target cancer cells or drug‐resistant bacterial infections (Szijártó et al , ; de Jong et al , ). Despite its crucial role in immunity, it is currently not understood how the MAC kills bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the unique lipopolysaccharide (LPS) O antigen O25b, which is conserved in the ST131- H 30 clonal lineage, represents an attractive molecular target that is accessible through various capsular polysaccharides. Due to this, O25b-specific MAbs were shown to be suitable for diagnostic purposes ( 24 ); furthermore, evidence was provided for their prophylactic efficacy ( 25 ). In this study, we corroborate a high protective efficacy of a selected humanized O25b MAb (A1124) in various rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, mAb was used in single dosage. The anti-bacterial experiments were performed only in accordance with the dose according to the reference, 16 and no more therapeutic dose gradient was designed. All of these are needed to supplement in later experiments.…”
Section: Discussionmentioning
confidence: 99%